SIḤR AND THE MUSLIM CREED: A THEOLOGICAL APPRAISAL OF IBN ʿABDIL WAHHĀB’S DISCOURSE AND ITS CONTEMPORARY IMPLICATIONS IN ILORIN - Olalekan Azeez, Raheed; Sambo, Adam (Program Studi Pendidikan Agama Islam, 2025)
Belief in and engagement with Siḥr (magic or sorcery) remains a persistent feature of religious life in many Muslim communities, particularly in sub-Saharan Africa, where Islamic orthodoxy often coexists with indigenous cosmologies. In Ilorin, Nigeria—a historically significant Islamic centre—practices associated with Siḥr continue to thrive despite the city’s deep-rooted Sunni heritage. This phenomenon poses a theological contradiction to classical reformist doctrines, notably those advanced by Shaykh Muḥammad Ibn ʿAbdil Wahhāb in Kitāb at-Tawḥīd, where Siḥr is categorically condemned as an act of Shirk (polytheism) and a nullifier of Tawḥīd (Islamic monotheism). The paper critically examines the discourse on Siḥr in Kitāb at-Tawḥīd and assesses its relevance to the beliefs and practices of Muslims in Ilorin. The research adopts a textual-analytical and expository method, rooted in classical Islamic scholarship, complemented by socio-anthropological interpretation based on informal field interviews and observed ritual patterns. It also integrates Cultural Schema Theory and Cognitive Anthropology to explain how theological doctrines are negotiated in local religious contexts. Findings reveal that various forms of Siḥr—such as love magic, separation rituals, economic charms, and protective amulets—are practised by Muslims across sectarian lines, including Sunni, Sufi, and Shia orientations. These practices are often justified through localised interpretations of spirituality, gender roles, and moral intention. The paper concludes that Siḥr in Ilorin reflects a pluralistic religious consciousness, where cultural resilience often challenges doctrinal rigidity. This research contributes to Islamic studies and religious anthropology by offering a contextual and interdisciplinary perspective on belief and ritual in contemporary Muslim societies.